The Relationships among Fear of Covid-19, Health Consciousness, Attitude toward Supplements, and Purchase Intention Using a Moderated Mediation Analysis - Uysal, Adem (Eskisehir Osmangazi Univ, Fac Education, 2023)
The purpose of this study is to examine the relationship between fear of Covid-19 (FoC), attitudes toward supplements (AtS), health consciousness (HC), and purchase intention (PI) by using moderated mediation analysis. The data acquired from 308 customers via faceto-face surveys were analyzed using descriptive statistics and structural equation modeling, and the process model produced by Hayes tested the hypotheses. The results show that the variable of AtA partially mediated the association between FoC and purchase intention. Health consciousness moderates the strength of the relationships between FoC and PI mediated by AtS. According to this, the influence of fear of Covid-19 on purchase intention via the attitudes toward food supplements differs according to consumers' health consciousness (low vs. high). The study provides essential cues for researchers, marketers, and advertisers of food supplements during the COVID-19 pandemic.
Keywords: Fear Of Covid-19; Attitudes Toward Supplements; Purchase Intention; Health Consciousness; T?Rkiye; Advertising Effectiveness; Consumer Attitudes; Nutrition; Ad